TRANSFORMATION IN THE INTERNET OF THINGS (IOT) MARKET IN THE BANKING SECTOR: A CASE STUDY OF TECHNOLOGY IMPLEMENTATION FOR SERVICE IMPROVEMENT AND TRANSACTION SECURITY - Aripin, Zaenal; Saepudin, Didin; Yulianty, Farida (Journal of Jabar Economic Society Networking Forum, 2024)
The transformation in the Internet of Things (IoT) market has become the primary focus of research and innovation in the banking sector, especially since the onset of the COVID-19 pandemic in 2019. Changes in consumer behavior towards online shopping and integrated payment activities have compelled the banking sector to strengthen its technological infrastructure to meet the demands of an increasingly complex market. Amidst this dynamism, the implementation of technologies such as blockchain and IoT has become crucial in enhancing services and transaction security in the banking sector. The aim of this research is to explore the impacts and challenges faced by the banking sector in adopting IoT technology to improve services and transaction security. This study utilizes a descriptive qualitative approach, involving literature analysis and case studies of IoT technology implementation in several leading banks. The research method involves collecting data from various sources, including scientific journals, articles, and relevant books. Data is also collected through interviews with experts and practitioners in the banking sector who have experience in implementing IoT technology. The results of the research indicate that the implementation of IoT technology in the banking sector has successfully improved the efficiency of transaction services. The use of IoT sensors and connected devices has enabled banks to automate transaction processes and accelerate responses to customer demands. Furthermore, blockchain technology has also brought significant improvements in transaction security by providing decentralized data structures that cannot be manipulated. Despite its success, the study also identifies several challenges in adopting IoT technology in the banking sector, including high implementation costs, complexity in integrating with existing infrastructure, and the need for a deep understanding of this technology. However, with strategic and planned steps, the banking sector can overcome these challenges and harness the full potential of IoT technology to create a better transaction experience for customers and the overall community.